Amplitude of vortical turbulence in crossed fields in separator of spent nuclear fuel at optimum parameters - Levchuk, I.P.; Maslov, V.I.; Onishchenko, I.N.; Yegorov, A.M.; Yuferov, V.B. (Вопросы атомной науки и техники, 2016)
Properties and excitation of the vortical turbulence, excited in a cylindrical radially inhomogeneous plasma in
crossed radial electric and longitudinal magnetic fields of separator of spent nuclear fuel, are considered. The
dispersion relation, which describes the vortical turbulence excitation, has been derived in the case of magnetized
ions. The expression for the vortex amplitude of saturation has been derived. Condition, at which vortical turbulence
is not excited, has been derived. It has been shown that the optimum value of the magnetic field, at which turbulence
is not excited, is proportional to the square root of the ion mass. Рассматриваются свойства и возбуждение вихревой турбулентности, возбуждаемой в цилиндрической
радиально неоднородной плазме в скрещённых радиальном электрическом и продольном магнитном
полях сепаратора отработанного ядерного топлива. Дисперсионное соотношение, которое описывает
возбуждение вихревой турбулентности, получено в случае замагниченных ионов. Получено выражение
для амплитуды насыщения вихрей. Найдено условие, при выполнении которого турбулентность не
возбуждается. Показано, что величина оптимального магнитного поля, при которой турбулентность не
возбуждается, пропорциональна корню квадратному из массы ионов. Розглядаються властивості і збудження вихрової турбулентності, яка збуджується в циліндричній
радіально неоднорідній плазмі в схрещених радіальному електричному і поздовжньому магнітному полях
сепаратору відпрацьованого ядерного палива. Дисперсійне співвідношення, яке описує збудження
вихрової турбулентності, отримано в випадку замагнічених іонів. Отримано вираз для амплітуди
насичення вихорів. Знайдено умову, при виконанні якої турбулентність не збуджується. Показано, що
величина оптимального магнітного поля, при якій турбулентність не збуджується, пропорційна кореню
квадратному з маси іонів.